2013
DOI: 10.1002/cncr.28306
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes with specific BRAF and NRAS mutations in patients with metastatic melanoma

Abstract: BACKGROUND: Hotspot mutations in BRAF and NRAS are the most common somatic events in patients with melanoma. These mutations occur at highly conserved residues, but include several different substitutions. To determine whether specific mutations are clinically important to differentiate, tumor characteristics and clinical outcomes were compared among patients with advanced melanoma with 1) BRAF V600E versus V600K mutations and 2) NRAS exon 1 versus exon 2 mutations. METHODS: Retrospective clinical and patholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
80
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 24 publications
12
80
0
5
Order By: Relevance
“…The data about BRAF V600 mutation which was accumulated following the discovery of this mutation in cancer by Davies et al (3) revealed that at least half of malignant melanomas (50 to 70%) may exhibit mutations in the BRAF V600 gene (1,2,7,10, 13-16) The BRAF V600E mutation constitutes more than 80% of BRAF mutations, and other BRAF mutations include V600K (1798 1799 GT > AA; 5% to 6%; valine to lysine), V600R (1798 1799 GT > AG; 1%; valine to arginine), V600E2 (1799 1800 AG > AA; 0.7%) and V600D (1799 1800 AG > AT) (1,4,6). Although it is said that the BRAF V600K mutation is rare, a few recent papers report higher rates of this mutation (20 to 44%) in some populations (6)(7)(8)15).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The data about BRAF V600 mutation which was accumulated following the discovery of this mutation in cancer by Davies et al (3) revealed that at least half of malignant melanomas (50 to 70%) may exhibit mutations in the BRAF V600 gene (1,2,7,10, 13-16) The BRAF V600E mutation constitutes more than 80% of BRAF mutations, and other BRAF mutations include V600K (1798 1799 GT > AA; 5% to 6%; valine to lysine), V600R (1798 1799 GT > AG; 1%; valine to arginine), V600E2 (1799 1800 AG > AA; 0.7%) and V600D (1799 1800 AG > AT) (1,4,6). Although it is said that the BRAF V600K mutation is rare, a few recent papers report higher rates of this mutation (20 to 44%) in some populations (6)(7)(8)15).…”
Section: Discussionmentioning
confidence: 99%
“…Other BRAF mutations include V600K (1798 1799 GT > AA; 5% to 6%; valine to lysine), V600R (1798 1799 GT > AG; 1%; valine to arginine), V600E2 (1799 1800 AG > AA; 0.7%) and V600D (1799 1800 AG > AT). Other rare mutations affecting various codons of the BRAF gene have also been described (1,4,6). Although the BRAF V600K mutation is said to be rare, a few recent papers have reported an occurrence rate of this mutation as high as 20% in some populations (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Melanoma is relatively more common in Caucasian populations and hence analyses of characteristics of patients with BRAF mutations in detail have been restricted to these patients 5, 6. Studies involving China, Korea and Japan revealed that there may be some differences in incidence of melanoma compared with the findings in Caucasians, including frequency and an age association with BRAF mutation 7, 8, 9, 10.…”
Section: Introductionmentioning
confidence: 99%